2014
DOI: 10.1111/bcpt.12182
|View full text |Cite
|
Sign up to set email alerts
|

Addiction‐Related Effects of DOV 216,303 and Cocaine: A Comparative Study in the Mouse

Abstract: DOV 216,303, an inhibitor of serotonin, noradrenaline and dopamine reuptake, belongs to a new line of drugs called 'triple reuptake inhibitors' that have been proposed for treatment of depression. The addictive drug cocaine has similar mechanism of action and exerts rewarding effects by blocking reuptake of dopamine, leading to increased extracellular concentrations of dopamine in the nucleus accumbens. Thus, DOV 216,303 and other triple reuptake inhibitors might be speculated to exhibit abuse potential, limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…19 Interestingly, in a recent study DOV 21,947 (amitifadine), a TRI, has been shown to produce little to no abuse liability. 26 Be that as it may, any novel monoamine transporters blocker which includes dopaminergic activity such as a TRI, should undergo extensive abuse liability testing.…”
Section: Introductionmentioning
confidence: 99%
“…19 Interestingly, in a recent study DOV 21,947 (amitifadine), a TRI, has been shown to produce little to no abuse liability. 26 Be that as it may, any novel monoamine transporters blocker which includes dopaminergic activity such as a TRI, should undergo extensive abuse liability testing.…”
Section: Introductionmentioning
confidence: 99%
“…85 While 59 showed acute self-administration in mice similar to 27, it did not induce the place preference associated with cocaine at the same dose. 83 This result, combined with a pharmacokinetic profile of slow clearance, suggested a lower potential of 59 for addiction than 27. Compound 65 was found to show low abuse potential based on a visual analogue scale (VAS) drug-liking score comparable to placebo in a clinical trial with recreational stimulant users, consistent with its pharmacokinetic profile of slow absorption and elimination [t max , 10− 12 h; t 1/2 , 44−77 h].…”
Section: Tris/serotonin Norepinephrine Dopamine Reuptake Inhibitors (...mentioning
confidence: 99%
“…It is hypothesized that an optimal transporter occupancy is important for good efficacy. The concern about abuse liability of TRIs due to increased dopaminergic activity has been alleviated in recent studies demonstrating no such liability [16] , [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both DOV 21,947 and BMS-820836 indicated high level of safety and tolerability in human [18] , [19] . The concern related to dopamine activity in TRIs leading to addiction was alleviated in a recent study indicating that the racemic version of DOV 21,947 has much less addictive-like properties compared to cocaine [20] .…”
Section: Introductionmentioning
confidence: 99%